CrAg screening strategy reduces definitive sequelae in people living with HIV - Marcela de Faria Ferreira; Fabio Brito-Santos; Marcos de Abreu Almeida; Luciana Trilles; Marcia dos Santos Lazera (Discover Viruses)
Abstract Background Screenning cryptococcal antigen (CrAg) of people living with HIV (PLHIV) reduces the morbidity and development of cryptococcal meningitis, but recent publications shows that it does not reduce mortality when comparable with a negative CrAg population group. Furthermore, most articles on cryptococcosis do not consider the sequelae related to cases that develop the meningeal form and survive the infection. There are, until now, no Brazilian studies that address the definitive sequelae and quality of life related to cryptococcal meningitis. Objectives To access the effectiveness of CrAg screening routine in reducing lethality and definitive sequelae of PLHIV co-infected with cryptococcal meningitis in Rio de Janeiro, Brazil. Methods We reviewed cases of HIV-associated cryptococcal meningitis at the Instituto Nacional de Infectologia Evandro Chagas/Fiocruz, Rio de Janeiro, Brazil, from January 2009 to June 2019 and accessed data to compare case lethality and permanent disabilities before and after the implementation of the CrAg screening test in PLHIV with CD4 ≤ 200 cells/mm3. Two groups were analyzed: the first group diagnosed before the implementation of the CrAg screening test and the second group after the implementation of the CrAg screening test. Results The present study revealed that cryptococcal meningitis in our sample is more prevalent in men, with a mean age of 34 years and a mean CD4 count of 47 cells/mm3. The case fatality rate at 12 and 24 weeks showed no significant difference between the two groups. Mortality at 12 weeks was 12.5% in the first group and 19% in the second group (p-value = 0.68) and at 24 weeks it was 18.8% in the first group and 23.8% in the second group (p-value = 1). The CrAg screening strategy reduced the development of permanent disabilities through early diagnosis with a significant difference between the two groups (p-value = 0.003). Visual disturbances and mental confusion were symptoms significantly associated with the development of permanent disability (p-value 0.011 and 0.005, respectively). Conclusions CrAg screening, although it did not change the lethality of cryptococcal meningitis, was effective in preventing permanent sequelae in patients with meningitis through early diagnosis, necessary for a good quality of life for PLHIV who survive this coinfection.